Effects of systemic corticosteroid therapy on bone mineral density in patients with rheumatoid arthritis - Chung Nakandakari, Cecilia (1998)
A cross-sectional, case-control study in 180 patients with rheumatoid arthritis (RA), to determine the effect of systemic corticosteroid therapy on bone mineral density (BMD) was performed. Patients were divided in two groups : both the corticosteroid-treated group and the non-corticosteroid-treated group. Those with concomitant diseases or any therapy that could affect BMD, were excluded. We also controlled other variables such as: age, race, gender, and length of disease; use of methotrexate or calcium therapy; length of menopause, and harmful habits. The corticosteroid-treated group included 90 RA patients between 31 - 85 years-old (54,6 ± 11,8 years), receiving prednisone therapy: 2,5 - 10 mg/d (5,8 ± 2,0 mg/d), during 3 - 300 months (54 ± 71,1 months). Compared with controls, the corticosteroid users had no significant differences in BMD (g/cm2) at the lumbar spine (L2: 0,917 ± 0,173 vs. 0,930 ± 0,162; L3: 0,957 ± 0,187 vs. 0,969 ± 0,170; L4: 0,957 ± 0,187 vs. 0,969 ± 0,170; L2-L4: 0,937 ± 0,170 vs. 0,956 ± 0,166), femur (0,731 ± 0,143 vs. 0,761 ± 0,159), nor Ward‘s triangle (0,630 ± 0,176 vs. 0,679 ± 0,188). Despite, we found significant differences in trocanter BMD (0,617 ± 0,139 vs. 0,672 ± 0,145, p < 0,05) ,multiple linear regression analysis failed to show that difference. We concluded that in our RA patients who received low dose corticosteroid therapy, BMD was quite similar to that in the non corticosteroid treated patients.